A Simple Technique to Determine Interface Slip of Stud Connected SCC Girders - Prakash, A.; Lakshmanan, N.; Anandavalli, N.; Madheswaran, C.K.; Iyer, N.R.; Rajasankar, J. (Civil Engineering Dimension, 2012)
A simple technique is proposed to compute interface slip of stud connected steel-concrete composite (SCC) girders based on the results of a flexure test. The technique makes use of relative longitudinal displacement of the concrete slab and steel beam to calculate the interface slip. In the flexure test of a SCC girder, a cost-effective instrumentation arrangement consisting of mechanical dial gauges is used to measure the relative longitudinal displacement. Responses measured from experiments on SCC girders conducted by the authors are used for numerical implementation and validation of the technique. Alternatively, interface slip is also evaluated by applying an analytical model which is based on first principles of mechanics. The values of interface slip computed by using the proposed technique are found to have close correlation with those of the analytical model. The effect of edge restraint on slip due to friction between steel and concrete is also studied.